1998
DOI: 10.1021/bi971554q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Binding Site for a Low-Molecular-Weight Inhibitor of Plasminogen Activator Inhibitor Type 1 by Site-Directed Mutagenesis

Abstract: A novel low-molecular-weight inhibitor, AR-H029953XX, was developed from a known fibrinolytic compound, flufenamic acid, which prevented complex formation of human plasminogen activator inhibitor type 1 (PAI-1) with tissue plasminogen activator (tPA) by inhibition of PAI-1. To explore the binding site for AR-H029953XX, mutants of human PAI-1 were constructed by site-directed mutagenesis and were then expressed in CHO cells, purified, activated, and characterized. (1) PAI-1 with mutations in the reactive center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 26 publications
2
68
0
Order By: Relevance
“…Preparation of Native, Latent, and Cleaved PAI-1-Glycosylated recombinant PAI-1 spontaneously converts to the latent conformation with a half-life of 3 h under physiological conditions (4,11), but this may be increased to 100 h if it is stored at high salt concentration, low pH, and room temperature (41). Our purification protocol of PAI-1 was a modification of existing methods (42,43), and all the steps were carried out at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Native, Latent, and Cleaved PAI-1-Glycosylated recombinant PAI-1 spontaneously converts to the latent conformation with a half-life of 3 h under physiological conditions (4,11), but this may be increased to 100 h if it is stored at high salt concentration, low pH, and room temperature (41). Our purification protocol of PAI-1 was a modification of existing methods (42,43), and all the steps were carried out at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, these agents appear to act via several different mechanisms. For example, the small molecule AR-H029953xx has been suggested to bind near residues Arg-76 in ␣-hD and Arg-118 in the loop between ␣-hF and ␤-s1A, and it inhibited PAI-1 by preventing complex formation between PAI-1 and tPA (52). For another small molecule, PAI-039, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These associations have made PAI-1 an attractive pharmaceutical target. However, despite extensive studies, only a few small molecule inhibitors have been identified thus far (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), and the majority of these are poor pharmaceutical candidates as they have relatively low affinity for PAI-1 and are unable to inactivate PAI-1 bound to its plasma cofactor vitronectin.…”
mentioning
confidence: 99%